The Impact of Social Media Influencers on Consumer Behavior: A Comparative Analysis of Generation Z and Millennials Life Style - Ayuningtyas Y Hapsari; Pipin Sukandi; Gallang P Dalimunthe; Annisa Lisdayanti; Yelli Eka Sumadhinata; Irma Nilasari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
In today’s digital age, social media has become an integral part of marketing strategies. One of the most trending research topics in the field of marketing is the impact of social media influencers on consumer behavior, particularly among Generation Z (Gen Z) and Millennials. These two generations have grown up with social media and are heavily influenced by the content they consume on these platforms. The primary objective of this research would be to examine and compare the effects of social media influencers on the purchasing decisions of Gen Z and Millennials. This could involve analyzing data from various sources, such as social media platforms, surveys, and sales figures. Additionally, the study could explore the types of influencers that are most effective in engaging these two generations, the specific content that resonates with them, and the role that trust and authenticity play in their decision-making processes.Furthermore, the research could delve into the psychological aspects of social media influencer marketing, such as the cognitive and emotional processes that underlie the formation of consumer preferences and attitudes. By understanding these mechanisms, marketers can develop more effective strategies to target Gen Z and Millennials, which are crucial demographics in today’s market.